African American Couples' Coparenting Satisfaction and Marital Characteristics in the First Two Decades of Marriage. (June 2015) - Riina, Elizabeth M.; McHale, Susan M.
This study charted the trajectory of coparenting satisfaction during the first and second decades of marriage and examined links between marital characteristics and coparenting satisfaction. Data came from a 3-year study of 145 African American mother–father dyads with pre- to late-adolescent-age offspring. Multilevel growth curves revealed an inverted U-shaped pattern of change in coparenting satisfaction; this effect was qualified by youth age such that the quadratic pattern was evident in families with older but not younger offspring. Controlling for cross-time averages of marital characteristics, changes in marital love were positively related, and changes in marital conflict were negatively related to changes in coparenting satisfaction, with stronger links for fathers than mothers. Interparental incongruence in childrearing attitudes moderated the effects of love, such that parents with more incongruent attitudes and lower levels of love reported the lowest levels of coparenting satisfaction.